ANALISIS OTONOMI DAERAH DALAM MENGUATKAN NEGARA KESATUAN REPUBLIK INDONESIA (STUDI TERHADAP UNDANG-UNDANG NOMOR 32 TAHUN 2004 JUNCTO UNDANG-UNDANG NO 12 TAHUN 2008 TENTANG PEMERINTAHAN DAERAH) - Enggarani, Nuria Siswi (Yustisia, 2013)
AbstractThis study aims to assess the regional autonomy in Indonesia in strengthening the republic of Indonesia based on Law No. 32/2004 and find a model that can strengthen the autonomy of the Unitary Republic of Indonesia. This research is normative law research that focused on the literature data. The approach used in this study is using the principles of law approach, systematic approach to legislation, research on the level of vertical synchronization, historical, as well as the hermeneutic approach using deductive research. data used in the study is from literature using primary and secondary materials. results of the study showed that affairs and supervision is the most important element in strengthening the framework of the Unitary State of the republic of Indonesia and is the basis for the implementation of special autonomy. Indicators used to determine that the Act No. 32/2004 can strengthen the republic of Indonesia or not is seen from the elements of affairs and supervision. If the writer sees affairs and the provisions of Law No. 32/2004 lead to the  interpreted assumption that lead to strengthen federalism and lead to recentralization model of autonomy that strengthen the unity of the State is to change the system of wide and broaden autonomy become wide autonomy, focused and responsibility. division System of the affair is defined for both the provincial government and local municipality government but it focuses on the reference to the distribution of the central and regional affair. The concurrent affairs division is only constitutes on government affairs in order to strengthen the unitary state republic of Indonesia. Using principles of decentralization, de-concentration and co-administration are done justly. Supervision of the implementation of obligatory affair is deleted because supervision has been done by the governor as a government representative. Form of autonomy that can strengthen Indonesia is local autonomy in the form of broaden autonomy and specific Autonomy or asymmetric decentralization.Keywords: regional Autonomy, strengthening, unitary state of the republic Indonesia, Law No. 32/2004.AbstrakPenelitian ini bertujuan mengkaji otonomi daerah di Indonesia dalam menguatkan Negara Kesatuan Republik Indonesia menurut UU No 32/2004 dan menemukan model otonomi daerah yang dapat menguatkan Negara Kesatuan Republik Indonesia. Penelitian ini merupakan penelitian hukum normatif memfokuskan pada data kepustakaan. Pendekatan yang dipergunakan dalam penelitian ini adalah menggunakan pendekatan asas-asas hukum, pendekatan sistematika peraturan perundang-undangan, penelitian terhadap taraf sinkronisasi vertical, sejarah serta menggunakan pendekatan Hermeneutic dengan menggunakan penalaran deduktif. Data penelitian yang digunakan adalah data dari studi kepustakaan yang berupa bahan hukum primer dan sekunder.Hasil kajian menunjukan bahwa, Urusan dan pengawasan merupakan elemen yang paling penting dalam rangka menguatkan Negara Kesatuan Republik Indonesia dan merupakan dasar bagi diterapkannya otonomi luas. Indikator yang digunakan untuk mengetahui bahwa UU No 32/2004 dapat menguatkan Negara Kesatuan Republik Indonesia atau tidak adalah dilihat dari elemen urusan dan pengawasan. Jika penulis melihat urusan dan pengawasan dalam ketentuan UU No 32/2004 menimbulkan asumsi penafsiran yang mengarah pada kecenderungan menguatkan kearah ke federalisme dan mengarah resentralisasi Model otonomi yang menguatkan Negara kesatuan terletak dengan mengubah system otonomi seluas-luasnya menjadi otonomi luas, focus dan bertanggung jawab. Sistem pembagian urusan diperincibaik bagi pemerintah daerah provinsi dan pemerintah daerah kabupaten/kota tetapi focus sesuai dengan  acuan dalam penyusunan system pembagian urusan pusat dan daerah. Pembagian urusan yang bersifat concurrent   hanyaterletak padaurusan pemerintah dalam rangka menguatkan Negara Kesatuan Republik Indonesia. Penggunaan asas desentralisasi, dekonsentrasi dan tugas pembantuan dilakukan secara seimbang. Pengawasan terhadap pelaksanaan urusan wajib, dihapus karena pengawasan telah dilakukan oleh gubernur sebagai wakil pemerintah. Bentuk otonomi yang dapat menguatkan Negara kesatuan republik indonesia adalah otonomi daerah dalam bentuk otonomi luas dan Otonomi Khusus atau desentralisasi asimetris.Kata kunci: Otonomi daerah, penguatan, Negara Kesatuan republik Indonesia, UU No 32/2004.